Epidemiological monitoring of the hospital environment: control of antibiotic-resistant strains isolated from patients in primary health care settings - Kosilova, Olha; Herasimenko, Olha; Novikov, Sergiy; Raylian, Marina; Volyansky, Dmytro (Annals of Mechnikov's Institute, 2025)
Antibiotic resistance is not a new phenomenon in modern medical practice. However, today this problem is becoming critical in healthcare. Over several decades, pathogens of common infections have developed various resistance genes, which has subsequently become a global issue. Epidemiological surveillance is a critically important tool in the fight against antibiotic resistance, as it provides systematic monitoring of the spread of resistant strains and their sensitivity to antimicrobial drugs. Epidemiological monitoring data enable the timely detection of new resistance mechanisms, tracking of trends in their spread, and development of effective strategies for infection control and rational antibiotic therapy. The aim: Objective: to monitor the prevalence of hospital-acquired infection pathogens and study their antibiotic resistance. Materials and methods. The study analysed the results of epidemiological monitoring of the structure and antibiotic resistance of microflora in a hospital environment. Microorganisms were isolated using standard methods with simple and special nutrient media. The WHONET 5.6 system was used as an information base for epidemiological surveillance. Results. The article presents the results of microbiological monitoring for 2023-2024. The main focus was on identifying the structure of nosocomial infection pathogens and assessing their antibiotic resistance. The bacteriological study covered more than 800 isolates, among which Staphylococcus spp. (49.6%), Candida albicans (28.7%) and representatives of the Enterobacteriaceae family (21.1%) dominated. High levels of resistance to key groups of antimicrobial drugs (β-lactams, fluoroquinolones, macrolides) were recorded in E. coli (80,0–100,0 %), Klebsiella pneumoniae (50,0–100,0 %), Pseudomonas aeruginosa (100,0 %), and Staphylococcus coagulase negative (78,8 %). The data obtained indicate the significant role of the hospital environment as a reservoir of multidrug-resistant microflora and point to the need for a comprehensive approach to infection control. Conclusions. The feasibility of local microbiological surveillance, adaptation of antibiotic therapy protocols taking into account local resistance profiles, and systematic staff training has been substantiated. Given the changing biological properties of pathogens and the growing threat of antibiotic resistance, it is extremely important to comprehensively implement sanitary and epidemiological measures and use antimicrobial agents appropriately.